Is Ferdinand Marcos a political genius - Marley, Ross (Pilipinas : a journal of Philippine studies, 1985)
President Ferdinand Marcos has dominated the Philippine political scene for twenty years, but his spectacular and dramatic career has attracted remarkably little analysis. This paper starts from the premise that one can learn much about Philippine politics by studying Marcos' tactics. his rise to power in the "Old Society" and his dictatorial rule since 1972 are explained by his mastery of the Philippine political culture as much as by his resort to naked force when needed.